Lietuvos įvaizdis - Fainaitė, Ester (Information & Media, 1996)
This article deals with some contemporary problems of Lithuania's image in the world. The importance of an appropriate country image is described in historical perspective.The main aim of this article is to discuss Lithuania's first public relations (PR) campaign to win United States recognition of its independence after World War I. The PR campaign was initiated by the Lithuanian National Council and organized by Carl Byoir and Edward L. Bernays. The main aspects and principles of the Lithuanian PR campaign are represented. The success of this campaign is explained as an excellent work of two public relations professionals, based on their experience and techniques developed in the Public Information Committee.